Management of granulomatous lobular mastitis: An international multidisciplinary consensus (2021 edition) (vol 9, 20, 2022) - Yuan, Qian-Qian; Xiao, Shu-Yuan; Farouk, Omar; Du, Yu-Tang; Sheybani, Fereshte; Tan, Qing Ting; Akbulut, Sami; Çetin, Kenan; Alikhassi, Afsaneh; Yaghan, Rami Jalal; Durur Subaşı, Irmak; Altıntoprak, Fatih; et al. (BMC, 2022)
[Abstract Not Available]
Correction: Management of granulomatous lobular mastitis: an international multidisciplinary consensus (2021 edition) (Military Medical Research, (2022), 9, 1, (20), 10.1186/s40779-022-00380-5)
Keywords: Management of Granulomatous; Lobular Mastitis; An International Multidisciplinary